1971
DOI: 10.1044/jshr.1401.05
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Auditory-Visual Equivalences

Abstract: A retarded boy, unable to read printed words orally or with comprehension, could match spoken words to pictures and could name pictures. After being taught to match spoken to printed words, he was then capable of reading comprehension (matching the printed words to pictures) and oral reading (naming the printed words aloud).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
460
0
214

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(696 citation statements)
references
References 0 publications
22
460
0
214
Order By: Relevance
“…Verbs, however, may not be the only verbal relations imposed by subjects during conditional discrimination training. Previous research has shown that verbal competent subjects often impose a common name to the members of equivalence classes (Mackay & Sidman, 1984;Sidman, 1971;Sidman & Cresson, 1973), and that such naming may facilitate equivalence effects (Dugdale & Lowe, 1990;Eikeseth & Smith, 1992). Thus, studies of stimulus equivalence with verbal subjects, meant to model how the direct establishment of specific conditional discriminations can give rise to meaning, syntactic relations, ordinal sequencing, and the like, are not necessarily pure demonstrations of such processes; they may depend on an already established meaning of a verb or a name operative in an experimentally uncontrolled self-instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Verbs, however, may not be the only verbal relations imposed by subjects during conditional discrimination training. Previous research has shown that verbal competent subjects often impose a common name to the members of equivalence classes (Mackay & Sidman, 1984;Sidman, 1971;Sidman & Cresson, 1973), and that such naming may facilitate equivalence effects (Dugdale & Lowe, 1990;Eikeseth & Smith, 1992). Thus, studies of stimulus equivalence with verbal subjects, meant to model how the direct establishment of specific conditional discriminations can give rise to meaning, syntactic relations, ordinal sequencing, and the like, are not necessarily pure demonstrations of such processes; they may depend on an already established meaning of a verb or a name operative in an experimentally uncontrolled self-instruction.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of stimulus equivalence, first outlined by Sidman (Sidman, 1971(Sidman, , 1990(Sidman, , 1994(Sidman, , 2000Sidman & Tailby, 1982), has been put forward as a behavioural process that may help to shed some light on situations where the behaviors are apparently 'emergent' (i.e., cannot be traced to direct contingencies: e.g., Follette, 1998;Pilgrim & Galizio, 2000;Saunders & Green, 1999). The stimulus equivalence paradigm has been employed to demonstrate how relations can emerge between stimuli that were not directly trained or paired together and also to suggest that the phenomenon of stimulus equivalence appears to be closely related to language or verbal processes (e.g., Barnes, 1994;Barnes-Holmes, Barnes-Holmes, Smeets, Cullinan & Leader, 2004;Sidman, 1994).…”
mentioning
confidence: 99%
“…Verbal organisms are uniquely able to bidirectionally relate stimuli whose relationship has been trained in only one direction. For example, when trained to choose B1 (from the group Bi, B2, B3) given Al, verbal humans will, without direct training, relate those stimuli in the other direction (i.e., will choose Al from Al, A2, A3, given Bi; e.g., Sidman, 1971;Sidman, Cresson, & Willson-Morris, 1974). This untrained relating is called a derived relation (in this case one of symmetry).…”
Section: Targeting the Discriminative Stimulusmentioning
confidence: 99%